Systems and Networks: An Ethnographic Case Study - Vasan, Mani Le (Journal of Modern Languages, 2017)
This study considers the E-mail writing. The paper indocates that in teaching of written discourse, it is possible to replicate some of the activities because writing is a time delayed activity and therefore can be done in the classroom, provided community values (already identified above) are in place. While this is true for most of the genres in written business discourse, it does not hold true for E-mail which is not a time delayed activity most of the time. The fleeting yet semi-permanent nature of the Email makes it an enigma that warrants researching into. The findings indicate that more research is needed into E-mail.